2007
DOI: 10.1002/path.2212
|View full text |Cite
|
Sign up to set email alerts
|

A candidate precursor to serous carcinoma that originates in the distal fallopian tube (J Pathol 2007; 211: 26–35)

Abstract: In this recent paper, the frequency of p53 signatures in the fallopian tubes of BRCA + women was recorded as 24% (10/24), in contrast to women with other disorders, which was 33% (19/58). We have since discovered that a proportion of the cases originally classified as BRCA + in our high-risk population had not been documented genetically as having a BRCA mutation. To address this error, we reviewed p53 immunostains from 605 tissue blocks of 75 consecutive prophylactic salpingectomies from women with documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Not surprisingly, no marker in this group separated STINs or HGSCs from SCOUTs. This is in contrast to other published markers such as Ki67, cyclin E, p16, and others, which are significantly more commonly expressed in STINs and HGSCs relative to benign Fallopian tube mucosa .…”
Section: Resultscontrasting
confidence: 93%
See 3 more Smart Citations
“…Not surprisingly, no marker in this group separated STINs or HGSCs from SCOUTs. This is in contrast to other published markers such as Ki67, cyclin E, p16, and others, which are significantly more commonly expressed in STINs and HGSCs relative to benign Fallopian tube mucosa .…”
Section: Resultscontrasting
confidence: 93%
“…The serous carcinogenic sequence involves not only frank malignancies with metastatic spread, but also serous cancer precursors, including latent precursors – the p53 signature – and serous tubal intraepithelial neoplasms (STINs). The latter include intramucosal carcinomas (STICs) and lesser but immunophenotypically similar atypias that are considered premalignant intraepithelial lesions (STILs) . Virtually all serous cancer precursors contain mutations in TP53 , evidence of a DNA damage response (γ‐H2AX p ), and predominate in the distal Fallopian tube .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing the fallopian tubes during such surgery, pathologists typically gave them only a cursory look, so the significance of these STIC lesions wasn't clear at first. When Christopher Crum, a pathologist at Brigham and Women's Hospital in Boston, Massachusetts, decided to look at these structures more systematically in the mid-2000s, he and his team found that STIC lesions were widespread in the fallopian tubes of people with ovarian cancer risk genes, especially at the end nearest the ovary 5 . "That was really the 'flip the table' moment," says Ronny Drapkin, a gynaecological pathologist at the University of Pennsylvania in Philadelphia, who worked on Crum's study.…”
Section: Missing Linksmentioning
confidence: 99%